2007
DOI: 10.1111/j.1365-2133.2007.07796.x
|View full text |Cite
|
Sign up to set email alerts
|

Olopatadine hydrochloride accelerates the recovery of skin barrier function in mice

Abstract: These results suggest that systemic administration of olopatadine accelerates the recovery of skin barrier function and ameliorates the adverse effects of topical steroids on skin barrier recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Moisturizers have less anti-inflammatory activity than PPARα activators, and while topical calcineurin inhibitors display significant anti-inflammatory effects, they compromise both epidermal permeability-barrier functions and antimicrobial barrier function in mice (Kim et al ., 2009). The oral administration of olopatadine hydrochloride has a positive effect on permeability barrier homeostasis and inflammation (Amano et al ., 2007; Tamura et al ., 2008), an observation that is consistent with the known ability of antihistamines (H1 and H2 blockers) to improve barrier function (Ashida et al ., 2001). However, it remains to be determined whether topical administration of olopatadine hydrochloride would also be effective for the treatment of AD, and in addition, it is unclear whether they can prevent the emergence of GC-related side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moisturizers have less anti-inflammatory activity than PPARα activators, and while topical calcineurin inhibitors display significant anti-inflammatory effects, they compromise both epidermal permeability-barrier functions and antimicrobial barrier function in mice (Kim et al ., 2009). The oral administration of olopatadine hydrochloride has a positive effect on permeability barrier homeostasis and inflammation (Amano et al ., 2007; Tamura et al ., 2008), an observation that is consistent with the known ability of antihistamines (H1 and H2 blockers) to improve barrier function (Ashida et al ., 2001). However, it remains to be determined whether topical administration of olopatadine hydrochloride would also be effective for the treatment of AD, and in addition, it is unclear whether they can prevent the emergence of GC-related side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, none of the FDA-approved antihistamines antagonize H3R or H4R at standard dosing regimens. In an epicutaneous allergen challenge murine AD model, treatment with the selective H1R antihistamine, olopatadine, not only suppressed inflammation and scratching by inhibiting cytokine/chemokine production (e.g., IL-31, TSLP, TARC) but also improved the skin barrier function [65,66,67,68,69]. Olopatadine has inhibitory effects on the release of inflammatory mediators (e.g., histamine, leukotriene, thromboxane, and tachykinins), which could explain these broad anti-allergic properties [70].…”
Section: Histamine Overviewmentioning
confidence: 99%
“…It has been reported that olopatadine attenuates (1) the elevation of various inflammatory cytokines in skin lesions, and (2) the scratching behavior in a mouse model of chronic contact dermatitis induced by repeated hapten challenge [28,29]. Furthermore, olopatadine accelerates the recovery of skin barrier function [30]. We evaluated the antineuritogenic and antipruritic effects of olopatadine in NC/Nga mice with dermatitis.…”
Section: Introductionmentioning
confidence: 99%